2014
DOI: 10.1111/ajo.12282
|View full text |Cite
|
Sign up to set email alerts
|

Study of accuracy of colposcopy in VIA and HPV detection‐based cervical cancer screening program

Abstract: Colposcopy performed well in the overall detection of cervical neoplasias, though its capability for accurate categorisation of degree of abnormality was poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 20 publications
2
38
0
Order By: Relevance
“…The failure to detect HSIL from colposcopy in the present study corresponded to a recent study from India (Ghosh et al, 2014). The Indian noted a very poor agreement with kappa only 0.17 between the colposcopic finding and the final histology of colposcopy in an HPV detection-based cervical cancer program of over 2000 women.…”
Section: Discussionsupporting
confidence: 55%
“…The failure to detect HSIL from colposcopy in the present study corresponded to a recent study from India (Ghosh et al, 2014). The Indian noted a very poor agreement with kappa only 0.17 between the colposcopic finding and the final histology of colposcopy in an HPV detection-based cervical cancer program of over 2000 women.…”
Section: Discussionsupporting
confidence: 55%
“…A few studies have reported the colposcopic accuracy of the IFCPC classification. The colposcopic sensitivity, specificity, PPV, and NPV for HSIL were reported to be 61.1%, 94.4%, 43.1%, and 77.9% in Hammes et al's study in 2007 when the 2002 nomenclature was used [14] and 84.8%, 66.1%, 10.3%, and 98.9% in Ghosh et al's study in 2014 when the 2011 nomenclature was used [16]. Our results with the 2011 nomenclature were appreciably better than the former study and showed lower sensitivity, higher specificity, much higher PPV, and equal NPV compared with the latter.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of the preceding 2002 nomenclature diagnosis and its reproducibility have been analyzed in some reports and good results were obtained [14, 15]. However, as for the applicability of the 2011 IFCPC terminology, evaluation studies are extremely scant [16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…Physician interpretation of colposcopy images (with both devices) agreed less frequently with histopathologic assessment than with each other. Previous studies have also demonstrated poor agreement between colposcopy and histopathology 18,19,20 .…”
Section: Discussionmentioning
confidence: 91%